Bioimaging: An Integrated Multifunctional Nanoplatform for Deep‐Tissue Dual‐Mode Imaging (Adv. Funct. Mater. 11/2018). (12th March 2018) - Yang, Fan; Skripka, Artiom; Benayas, Antonio; Dong, Xianke; Hong, Sung Hwa; Ren, Fuqiang; Oh, Jung Kwon; Liu, Xinyu; Vetrone, Fiorenzo; Ma, Dongling
Abstract : In article number1706235, Fiorenzo Vetrone, Dongling Ma, and co‐workers report a biocompatible multifunctional nanoplatform consisting of a superparamagnetic Fe3 O4 core and photoluminescent NaYF4 :Nd 3+ shell that can be excited and emit in the near‐infrared (NIR) range. Combination of the unique NIR (excitation)‐to‐NIR (emission) property with superparamagnetism makes the developed nanoplatform extremely promising for deep‐tissue dual‐mode (optical and magnetic resonance) bioimaging.